'Yellow skin, black hair … Careful, Tintin': Hergé and Orientalism. Issue 1 (16th February 2011) - Mountfort, Paul
This article frames Hergé's The Adventures of Tintin in terms of its treatment of ethnic, cultural and geographic Others. The series has been accused of bundling right wing, reactionary and racist viewpoints into its codes of visual representation and storylines. I argue that the pervasiveness of the series, its institutionalization in francophone culture, and its currency as a global franchise makes the question one of particular relevance at a time when big-budget productions by Steven Spielberg and Peter Jackson look set to further cement Tintin's place in popular culture. With other critics I see Tintin's Chinese adventure, The Blue Lotus (1934−1935), as central to addressing these concerns, as even though this fourth album in the series continues to perpetuate certain Orientalist assumptions it represents Hergé's first serious attempt to depict the Other in less than pejorative terms. What this article does is seek to place The Blue Lotus within the Adventures and their cultural-historical contexts, as well as the corresponding evolution of Herge's ideology, thus broadening the Orientalism of the title to encompass not only Asia and the Mideast but the subaltern and Europe's own 'internal Others'.